A high-strength cementitious material based on slag and a preparation method thereof

By adding modified fiber material and modified polyacrylamide resin material to the slag-based cementing material to form a composite structure, the problems of insufficient strength and unstable performance of cementing materials are solved, and its strength, waterproofness and corrosion resistance are significantly improved, and its application environment is expanded.

CN119241173BActive Publication Date: 2025-03-21HAINA MEITENG INTELLIGENT MFG (SHANDONG) CO LTD

Patent Information

Application Number
CN202411396270.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-03-21
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Slag-based cementing materials face problems of insufficient use strength and unstable performance in practical applications, especially due to poor stability caused by differences in slag composition, which affects their waterproof and corrosion resistance.

Method used

The composite structure is formed by adding modified fiber materials and modified polyacrylamide resins to improve the strength and stability of the cemented material.

Benefits of technology

It significantly improves the strength, waterproofness and corrosion resistance of cemented materials, alleviates the stability problems caused by differences in slag composition, and expands the application environment and field of cemented materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073840120000141
    Figure BDA0005073840120000141
  • Figure BDA0005073840120000151
    Figure BDA0005073840120000151
Patent Text Reader

Abstract

The present application relates to the field of cementitious materials, and in particular to a high-strength cementitious material based on slag and a preparation method thereof. The high-strength cementitious material based on slag, in parts by mass, comprises the following raw materials: 50 to 65 parts of blast furnace slag, 15 to 25 parts of Portland cement, 5 to 12 parts of fly ash, 10 to 20 parts of filler, 0.5 to 1 part of water reducer, 1 to 3 parts of reinforcing agent, 5 to 15 parts of resin material, 6 to 12 parts of sodium bentonite, and 20 to 40 parts of water. The cementitious material prepared in the present application not only has excellent material strength, but also can ensure good waterproofness, corrosion resistance, etc., and can effectively alleviate the problem of poor stability of the cementitious material caused by differences in slag composition, thereby effectively expanding the application environment and field of slag-based cementitious materials, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cementitious materials, and in particular to a high-strength cementitious material based on slag and a preparation method thereof. Background Art

[0002] With the acceleration of the global industrialization process, the generation of a large number of industrial by-products and waste has become an urgent problem to be solved. Among them, blast furnace slag, as an important industrial by-product, is produced in large quantities during the steel production process. The main components of slag include SiO2, CaO, Al2O3, etc., which have high potential activity. If these slags can be effectively utilized, it can not only reduce environmental pollution, but also save resources, and have important economic and social value.

[0003] In recent years, researchers have found that slag, after proper activation treatment, can be used as a raw material for cementitious materials to prepare high-performance concrete, mortar and other building materials. Compared with traditional cement-based materials, slag-based cementitious materials have higher strength, better durability and better environmental performance. Slag-based cementitious materials also show excellent resistance to chemical erosion, freeze-thaw resistance and carbonization resistance, which makes their application in harsh environments possible, such as marine engineering, chemical facilities, etc.

[0004] However, despite the many advantages of slag-based cementitious materials, they still face some technical challenges in practical applications. For example, the insufficient strength of the cementitious materials and the large differences in the composition of slag from different sources may lead to unstable performance of the final cementitious materials, affecting their application in actual engineering, including waterproofing, corrosion resistance and other properties.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a high-strength binder material based on slag and a preparation method thereof. The binder material prepared in the present application not only has excellent material strength, but also can ensure good waterproofness, corrosion resistance, etc., and can effectively alleviate the problem of poor stability of the binder material caused by differences in slag components, thereby effectively expanding the application environment and field of slag-based binder materials, and has very excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a high-strength binder material based on slag. The raw materials are, by mass: 50 to 65 parts of blast furnace slag, 15 to 25 parts of Portland cement, 5 to 12 parts of fly ash, 10 to 20 parts of filler, 0.5 to 1 part of water reducer, 1 to 3 parts of reinforcing agent, 5 to 15 parts of resin material, 6 to 12 parts of sodium bentonite, and 20 to 40 parts of water.

[0007] As a preferred solution, the mass ratio of blast furnace slag, silicate cement, fly ash and sodium bentonite is (55-65):(16-24):(7-10):(8-10).

[0008] As a preferred solution, the mass ratio of blast furnace slag, silicate cement, fly ash and sodium bentonite is (58-62):(20-23):(8-9):(9-10).

[0009] As a preferred solution, the mass ratio of the blast furnace slag, filler and resin material is (55-65): (15-20): (10-14).

[0010] As a preferred solution, the mass ratio of the blast furnace slag, filler and resin material is (58-62): (18-20): (12-14).

[0011] As a preferred solution, the blast furnace slag is steel plant blast furnace slag.

[0012] As a preferred solution, the blast furnace slag contains, by mass percentage, 30-35% SiO2, 35-40% CaO, 10-15% Al2O3, 5-8% MgO, and the balance is made up of CaCO3.

[0013] As a preferred solution, the silicate cement is Type I silicate cement.

[0014] As a preferred solution, the fly ash is Class I fly ash or Class II fly ash.

[0015] As a preferred solution, the filler is a composition of silicon dioxide and modified fiber material.

[0016] As a preferred solution, the mass ratio of the silicon dioxide to the modified fiber material is (3-5):(12-15).

[0017] As a preferred solution, the average particle size of the silicon dioxide is 30 to 50 nm.

[0018] As a preferred solution, the preparation method of the modified fiber material comprises the following steps: S1: adding glass fiber and carbon fiber to DMF solution, heating to 65-70°C and ultrasonically dispersing at 300-400W for 0.5-1h to obtain a mixed dispersion; S2: adding glutaric anhydride, sodium dodecylbenzene sulfonate and butyl titanate to the mixed dispersion, heating to 75-80°C, keeping warm and stirring for 2-3h, centrifuging and filtering the product after the reaction is completed, washing with methanol for 2-3 times, and then vacuum drying to obtain a pretreated Composite fiber material; S3: adding the pretreated composite fiber material and aluminum chloride to a mixed solution of DMF and deionized water, adding p-aminobenzoic acid, sealing the reaction container, controlling the pressure in the kettle to 1-1.2MPa, and stirring at 130-150°C and 60-100rpm for 13-15h; S4: then adding dicyclopentadiene and sodium ethoxide, and naturally cooling to 65-75°C, keeping warm and stirring for 2.5-3h, centrifugally filtering after the reaction is completed, and washing with methanol for 2-3 times, and then drying.

[0019] As a preferred solution, the mass ratio of the glass fiber, carbon fiber, glutaric anhydride, sodium dodecylbenzene sulfonate and butyl titanate is (3-4): (8-10): (2-2.5): (0.3-0.4): (0.2-0.25).

[0020] As a preferred solution, the mass ratio of the pretreated composite fiber material, aluminum chloride and p-aminobenzoic acid, dicyclopentadiene and sodium ethoxide is (5-5.5): (1.5-2): (1.1-1.4): (0.6-0.8): (0.02-0.04).

[0021] As a preferred solution, in the mixed solution of DMF and deionized water, the mass ratio of DMF to deionized water is (1-1.5):(3-4).

[0022] As a preferred solution, the average diameter of the glass fiber is 7-15 μm, and the average length is 5-8 mm.

[0023] As a preferred solution, the average diameter of the carbon fibers is 5 to 10 μm, and the average length is 3 to 6 mm.

[0024] In the present application, the strength, waterproofness and structural stability of the cementing material can be effectively improved by adding the above-mentioned modified fiber material. The added modified fiber can form a composite structure with a composite fiber of glass fiber and carbon fiber as the base, and the prepared framework particle structure is embedded therein, so as to form a linear composite structure with good surface group modification and internal stable framework particle support, and the existence of this structure can achieve a high-strength connection effect with the resin material and the slag powder in the cementing material, and when an external force acts, the force bearing upper limit of the cementing material can be greatly improved through the fiber connection force and the skeleton support force of the embedded framework particles, and when used in an aqueous environment, the low surface energy composite fiber surface it imparts can form a gradient barrier interface inside the cementing material, thereby greatly suppressing the penetration speed of water inside, improving the penetration resistance, and limiting the corrosion effect of the corrosive molecules and groups with water as the carrier on the cementing material, thereby improving the waterproof performance while ensuring the structural stability of the cementing material in normal use and in an aqueous environment.

[0025] As a preferred solution, the water reducer is any one of the polycarboxylic acid water reducers.

[0026] As a preferred solution, the enhancer is at least one of triethanolamine, ethylenediamine, isopropanol, aluminum sulfate and calcium chloride.

[0027] As a preferred solution, the enhancer is triethanolamine.

[0028] As a preferred solution, the resin material is modified polyacrylamide.

[0029] As a preferred solution, the preparation method of the modified polyacrylamide comprises the following steps: S1: adding styrene, glycidyl acrylate and butyl acrylate to an acryloyl chloride solution, introducing nitrogen, adding an initiator, heating to 80-90°C for reaction to generate a prepolymer product; S2: mixing the prepolymer product with N-hydroxymethyl acrylamide, deionized water and the initiator, and reacting for 4-6 hours after nitrogen fully replaces the reaction system gas to obtain a modified product solution; S3: adding triethanolamine to the modified product solution, and cooling naturally, then adding acetone for cyclic washing 2-3 times, and drying to obtain the product.

[0030] As a preferred solution, the mass ratio of styrene, glycidyl acrylate, butyl acrylate and N-hydroxymethyl acrylamide is (6-8): (1-2): (2-3): (30-35).

[0031] As a preferred solution, the amount of triethanolamine added is 0.5-1 wt % of the modified product solution.

[0032] As a preferred solution, the initiator is azobisisobutyronitrile.

[0033] The modified polyacrylamide resin material added in the present application can not only effectively improve the bonding strength of the adhesive material and provide better adhesion, but also form a good active connection with the added modified fiber material, effectively improving the connection and support function inside the adhesive material. On the other hand, the addition of the modified polyacrylamide resin material can form a good interface bond between the adhesive material and the substrate through its long chain structure, reduce interface defects, and weaken the problem of decreased bonding performance caused by the appearance of modified fibers on the surface. The modified polyacrylamide resin material added in the present application can greatly limit the free speed of water molecules inside the adhesive material through the presence of its long composite chain segments, increase the limiting resistance of water molecules, and thus prevent the rapid penetration and invasion of water. The multi-segment and multi-group activity inside the adhesive material can greatly increase the number of connection sites inside the adhesive material, and limit the probability of contact and collision of free groups inside, reduce the occurrence of internal reactions, and improve corrosion resistance, thereby obtaining excellent structural stability.

[0034] As a preferred solution, the sodium bentonite is coarse-grained sodium bentonite.

[0035] As a preferred solution, the average particle size of the coarse-grained sodium bentonite is 0.5 to 1.5 mm.

[0036] The second aspect of the present application provides a method for preparing the above-mentioned slag-based high-strength binder material, which specifically includes the following steps: S1: ball-milling blast furnace slag to a particle size of ≤0.1 mm, then mixing the blast furnace slag with all other raw materials except water and adding them to a mixer, stirring at a speed of 60-80 rpm for 15-20 minutes to obtain a mixture; S2: mixing the mixture with water, stirring at a speed of 50-60 rpm for 15-25 minutes until it becomes a uniform slurry, to obtain a mixed slurry; S3: pouring the mixed slurry into a pre-prepared mold, vibrating and compacting to remove bubbles, and curing at a temperature of 18-24°C and a relative humidity of 95-100% for 22-26 hours for initial curing. After demolding, continue to cure for 28 days, during which the temperature and humidity are kept constant, and the mixture is obtained after completion.

[0037] The beneficial effects of this application are:

[0038] 1. The high-strength slag-based cementitious material provided in the present application not only has excellent material strength, but also can ensure good waterproofness, corrosion resistance, etc., and can effectively alleviate the problem of poor stability of the cementitious material caused by differences in slag components, thereby effectively expanding the application environment and field of slag-based cementitious materials, and has very excellent application prospects.

[0039] 2. A high-strength slag-based binder material provided in the present application, the addition of modified fiber material can effectively improve the strength, waterproofness and structural stability of the binder material; the added modified fiber can form a composite structure with a composite fiber of glass fiber and carbon fiber as the base, and the prepared framework particle structure is embedded therein, thereby forming a linear composite structure with good surface group modification and stable framework particle support inside, the existence of this structure can achieve a high-strength connection effect with the resin material and the slag powder in the binder material, and when external force acts, the upper limit of the force bearing of the binder material can be greatly improved through the fiber connection force and the skeleton support force of the embedded framework particles, and when used in an aqueous environment, the low surface energy composite fiber surface imparted thereto can form a gradient barrier interface inside the binder material, thereby greatly inhibiting the penetration rate of moisture and corrosive molecules / groups inside, and improving the penetration resistance.

[0040] 3. The high-strength binder material based on slag provided in the present application, the added modified polyacrylamide resin material can not only effectively improve the bonding strength of the binder material and provide better adhesion, but also can form a good active connection with the added modified fiber material, effectively improving the internal connection and support of the binder material. On the other hand, the addition of modified polyacrylamide resin material can form a good interface bonding between the binder material and the substrate through its long-chain structure, reduce interface defects, and weaken the problem of decreased bonding performance due to the appearance of modified fibers on the surface. DETAILED DESCRIPTION

[0041] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0042] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0043] Example 1

[0044] Example 1 The first aspect provides a slag-based high-strength binder material, in which the raw materials are, by mass: 60.5 parts of blast furnace slag, 21.5 parts of Portland cement, 8.8 parts of fly ash, 19.5 parts of filler, 0.8 parts of water reducer, 2.2 parts of reinforcing agent, 12.8 parts of resin material, 9.5 parts of sodium bentonite, and 34 parts of water.

[0045] The blast furnace slag comes from a steel plant in Laiyang, Shandong. The contents of the blast furnace slag, by mass percentage, are: SiO2 32.4%, CaO 38.6%, Al2O3 11.7%, MgO 6.47%, and CaCO3 makes up the balance.

[0046] The silicate cement is Type I silicate cement; the fly ash is Class I fly ash.

[0047] The filler is a composition of silicon dioxide and modified fiber material, and the mass ratio of the two is 4:13.5.

[0048] The average particle size of silica was 36 nm.

[0049] The preparation method of the modified fiber material comprises the following steps, calculated by mass: S1: adding 3.7 parts of glass fiber and 9.6 parts of carbon fiber to 200 parts of DMF solution, heating to 65°C and ultrasonically dispersing at 400W for 1 hour to obtain a mixed dispersion; S2: adding 2.4 parts of glutaric anhydride, 0.35 parts of sodium dodecylbenzene sulfonate and 0.22 parts of butyl titanate to the mixed dispersion, heating to 80°C, keeping warm and stirring for 3 hours, and after the reaction is completed, centrifuging and filtering the product, washing it with methanol for 3 times, and then vacuum drying it to obtain a pretreated composite fiber material; S3: adding 5 .4 parts of pretreated composite fiber material and 1.8 parts of aluminum chloride are added to a mixed solution of DMF and deionized water (a total of 180 parts, the mass ratio of DMF to deionized water is 1:3), and after adding 1.2 parts of p-aminobenzoic acid, the reaction vessel is sealed to control the pressure in the kettle to 1MPa and stir at 140°C and 80rpm for 14h; S4: then add 0.75 parts of dicyclopentadiene and 0.024 parts of sodium ethoxide, and naturally cool to 70°C, keep warm and stir for 3h, centrifuge and filter after the reaction is completed, and wash with methanol for 3 times, and then dry.

[0050] The average diameter of the carbon fiber is 7.5 μm, and the average length is 4.6 mm. The carbon fiber is purchased from Shanghai Lishuo Composite Materials Co., Ltd. and has a corresponding size of chopped carbon fiber products.

[0051] The glass fibers had an average diameter of 10.8 μm and an average length of 7.5 mm, and were purchased from glass fiber products of corresponding sizes sold by Taian Haoda New Materials Co., Ltd.

[0052] The water reducer is a polycarboxylate water reducer, which was purchased from Shanghai Hengchuang Chemical Co., Ltd. and sold under the model PC-1022.

[0053] The enhancer is triethanolamine.

[0054] The resin material is modified polyacrylamide, and the preparation method comprises the following steps, calculated by weight: S1: adding 7.5 parts of styrene, 1.2 parts of glycidyl acrylate and 2.4 parts of butyl acrylate to 30 parts of acryloyl chloride solution, introducing nitrogen, adding 0.14 parts of azobisisobutyronitrile, heating to 85°C for reaction to generate a prepolymer product; S2: mixing the prepolymer product with 32.8 parts of N-hydroxymethyl acrylamide, 280 parts of deionized water and 0.22 parts of azobisisobutyronitrile, fully replacing the reaction system gas with nitrogen, reacting for 5 hours to obtain a modified product solution; S3: adding 0.8wt% (based on the total weight percentage of the modified product solution) of triethanolamine to the modified product solution, and cooling naturally, then adding acetone for cyclic washing twice, and drying to obtain the product.

[0055] The sodium bentonite is coarse-grained sodium bentonite; the average particle size of the coarse-grained sodium bentonite is 1.2 mm, and the product of the corresponding particle size is purchased from Dongguan Ruiheng Mineral Products Co., Ltd.

[0056] The second aspect of the present embodiment provides a method for preparing the above-mentioned slag-based high-strength binder material, which specifically includes the following steps: S1: ball-mill blast furnace slag to a particle size of 0.04 mm, then mix the blast furnace slag with all other raw materials except water and add them to a mixer, and stir at 80 rpm for 15 minutes to obtain a mixture; S2: mix the mixture with water, and stir at 60 rpm for 25 minutes until it becomes a uniform slurry to obtain a mixed slurry; S3: pour the mixed slurry into a pre-prepared mold, vibrate to compact it, remove bubbles, and cure it at 22°C and 98% relative humidity for 24 hours for initial curing. After demolding, continue to cure for 28 days, during which the temperature and humidity are kept constant. The mixture is obtained after completion.

[0057] Example 2

[0058] The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the slag-based high-strength binder material, in parts by mass, are: 65 parts of blast furnace slag, 16.5 parts of Portland cement, 10 parts of fly ash, 18 parts of filler, 0.8 parts of water reducer, 2.2 parts of reinforcing agent, 14 parts of resin material, 8 parts of sodium bentonite, and 34 parts of water.

[0059] Example 3

[0060] The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the slag-based high-strength binder material, in parts by mass, are: 55 parts of blast furnace slag, 24 parts of Portland cement, 7 parts of fly ash, 20 parts of filler, 0.8 parts of water reducer, 2.2 parts of reinforcing agent, 10 parts of resin material, 10 parts of sodium bentonite, and 34 parts of water.

[0061] Comparative Example 1

[0062] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the slag-based high-strength binder material, in parts by mass, are: 75 parts of blast furnace slag, 15.5 parts of Portland cement, 8.8 parts of fly ash, 22.8 parts of filler, 0.8 parts of water reducer, 2.2 parts of reinforcing agent, 5.5 parts of resin material, 9.5 parts of sodium bentonite, and 36 parts of water.

[0063] Comparative Example 2

[0064] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the slag-based high-strength binder material, in parts by mass, are: 60.5 parts of blast furnace slag, 21.5 parts of Portland cement, 8.8 parts of fly ash, 8.2 parts of filler, 0.8 parts of water reducer, 2.2 parts of reinforcing agent, 18.8 parts of resin material, 9.5 parts of sodium bentonite, and 34 parts of water.

[0065] Comparative Example 3

[0066] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of silicon dioxide and modified fiber material, and the mass ratio of the two is 8:5.

[0067] Comparative Example 4

[0068] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber material comprises the following steps, calculated by mass: S1: adding 1.5 parts of glass fiber and 12 parts of carbon fiber to 200 parts of DMF solution, heating to 65°C and ultrasonically dispersing at 400W for 1h to obtain a mixed dispersion; S2: adding 1.2 parts of glutaric anhydride, 0.15 parts of sodium dodecylbenzene sulfonate and 0.11 parts of butyl titanate to the mixed dispersion, heating to 80°C, keeping warm and stirring for 3h, after the reaction is completed, centrifuging and filtering the product, washing with methanol for 3 times, and vacuum drying to obtain Pre-treat the composite fiber material; S3: add 5.4 parts of the pre-treated composite fiber material and 1.8 parts of aluminum chloride to a mixed solution of DMF and deionized water (a total of 180 parts, the mass ratio of DMF to deionized water is 1:3), add 1.2 parts of p-aminobenzoic acid, seal the reaction vessel, control the pressure in the kettle to 1MPa, and stir at 140°C and 80rpm for 14h; S4: then add 0.75 parts of dicyclopentadiene and 0.024 parts of sodium ethoxide, and naturally cool to 70°C, keep warm and stir for 3h, centrifuge and filter after the reaction is completed, and wash with methanol for 3 times, and then dry.

[0069] Comparative Example 5

[0070] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified fiber material comprises the following steps, calculated by mass: S1: adding 3.7 parts of glass fiber and 9.6 parts of carbon fiber to 200 parts of DMF solution, heating to 65°C and ultrasonically dispersing at 400W for 1h to obtain a mixed dispersion; S2: adding 2.4 parts of glutaric anhydride, 0.35 parts of sodium dodecylbenzene sulfonate and 0.22 parts of butyl titanate to the mixed dispersion, heating to 80°C, keeping warm and stirring for 3h, after the reaction is completed, centrifuging and filtering the product, washing with methanol for 3 times, and then vacuum drying to obtain To pre-treat the composite fiber material; S3: add 8.8 parts of the pre-treated composite fiber material and 1.1 parts of aluminum chloride to a mixed solution of DMF and deionized water (a total of 180 parts, the mass ratio of DMF to deionized water is 1:3), add 0.8 parts of p-aminobenzoic acid and seal the reaction vessel to control the pressure in the kettle to 1MPa and stir at 140°C and 80rpm for 14h; S4: then add 0.32 parts of dicyclopentadiene and 0.011 parts of sodium ethanol, and naturally cool to 70°C, keep warm and stir for 3h, centrifuge and filter after the reaction is completed, and wash with methanol for 3 times, and then dry.

[0071] Comparative Example 6

[0072] The specific implementation of this comparative example is basically the same as that of Example 1, except that the resin material is modified polyacrylamide, and the preparation method comprises the following steps, calculated by mass: S1: adding 15 parts of styrene, 0.5 parts of glycidyl acrylate and 1 part of butyl acrylate to 30 parts of acryloyl chloride solution, introducing nitrogen, adding 0.18 parts of azobisisobutyronitrile, heating to 85°C and reacting to generate a prepolymer product; S2: mixing the prepolymer product with 40 parts of N-hydroxymethyl acrylamide, 280 parts of deionized water and 0.22 parts of azobisisobutyronitrile, and reacting for 5 hours to obtain a modified product solution after nitrogen fully replaces the reaction system gas; S3: adding 0.8wt% (based on the total mass percentage of the modified product solution) of triethanolamine to the modified product solution, and naturally cooling, then adding acetone for cyclic washing twice, and drying to obtain the product.

[0073] Comparative Example 7

[0074] The specific implementation of this comparative example is basically the same as that of Example 1, except that the resin material is modified polyacrylamide, and the preparation method comprises the following steps, calculated by mass: S1: adding 3.5 parts of styrene, 5.5 parts of glycidyl acrylate and 5.5 parts of butyl acrylate to 30 parts of acryloyl chloride solution, introducing nitrogen, adding 0.14 parts of azobisisobutyronitrile, heating to 85°C and reacting to generate a prepolymer product; S2: mixing the prepolymer product with 24.5 parts of N-hydroxymethyl acrylamide, 240 parts of deionized water and 0.21 parts of azobisisobutyronitrile, and reacting for 5 hours to obtain a modified product solution after nitrogen fully replaces the reaction system gas; S3: adding 0.8wt% (based on the total mass percentage of the modified product solution) of triethanolamine to the modified product solution, and cooling naturally, then adding acetone for cyclic washing twice, and drying to obtain the product.

[0075] Performance Evaluation

[0076] Anti-penetration pressure: The anti-penetration pressure test was carried out on the cementing materials obtained in the examples and comparative examples with reference to the standard GB / T 50082-2009. The results were expressed as the maximum water-free pressure. The test value was the average value of 10 tests and recorded in Table 1.

[0077] Compressive strength: The mechanical strength of the bonding materials obtained in the embodiments and comparative examples was tested with reference to the standard GB / T 50081-2019, and the test values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0078] Anti-corrosion performance: With reference to "Concrete Anti-Sulfate Corrosion Preservatives" JC / T 1011-2006, the 28d corrosion resistance coefficient and 28d expansion rate of the bonding materials obtained in the examples and comparative examples were tested, and the measured values ​​were taken as the average value of 10 tests and recorded in Table 1.

[0079] Table 1 Performance test results

[0080]

[0081]

[0082] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of compression resistance, waterproof performance and corrosion resistance. This is mainly due to the combined effect of the modified fiber material, modified resin material and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A high-strength cementitious material based on slag, characterized in that: The raw materials are as follows: 50-65 parts of blast furnace slag, 15-25 parts of Portland cement, 5-12 parts of fly ash, 10-20 parts of filler, 0.5-1 parts of water reducer, 1-3 parts of reinforcing agent, 5-15 parts of resin material, 6-12 parts of sodium bentonite, and 20-40 parts of water. The filler is a composition of silicon dioxide and modified fiber material; the average particle size of the silicon dioxide is 30 to 50 nm; The mass ratio of the silicon dioxide to the modified fiber material is (3-5): (12-15); Preparation method of modified fiber material The following steps are involved: S1: adding glass fiber and carbon fiber to DMF solution, heating to 65-70°C, and ultrasonically dispersing at 300-400W for 0.5-1h to obtain a mixed dispersion; S2: adding glutaric anhydride, sodium dodecylbenzene sulfonate and butyl titanate to the mixed dispersion, and heating to 75-80°C, stirring for 2-3h, centrifugally filtering the product after the reaction is completed, washing with methanol for 2-3 times, and then vacuum drying to obtain a pretreated composite fiber material; S3: adding the pretreated composite fiber material and aluminum chloride to a mixed solution of DMF and deionized water, adding p-aminobenzoic acid, sealing the reaction vessel, controlling the pressure in the kettle to 1-1.2 MPa, and stirring at 130-150° C. and 60-100 rpm for 13-15 hours; S4: adding dicyclopentadiene and sodium ethoxide, and naturally cooling to 65-75° C., stirring and reacting for 2.5-3 hours at this temperature, centrifugally filtering after the reaction is completed, washing with methanol 2-3 times, and drying to obtain the product; The mass ratio of the glass fiber, carbon fiber, glutaric anhydride, sodium dodecylbenzene sulfonate and butyl titanate is (3-4): (8-10): (2-2.5): (0.3-0.4): (0.2-0.25); The mass ratio of the pretreated composite fiber material, aluminum chloride and p-aminobenzoic acid, dicyclopentadiene and sodium ethoxide is (5-5.5): (1.5-2): (1.1-1.4): (0.6-0.8): (0.02-0.04); The average diameter of the carbon fiber is 5 to 10 μm, and the average length is 3 to 6 mm; The water reducer is any one of the polycarboxylate water reducers; The resin material is modified polyacrylamide; Preparation method of modified polyacrylamide The following steps are involved: S1: adding styrene, glycidyl acrylate and butyl acrylate to acryloyl chloride solution, introducing nitrogen, adding initiator, heating to 80-90°C for heating reaction to generate prepolymer product; S2: mixing the prepolymer product with N-hydroxymethyl acrylamide, deionized water and initiator, and after nitrogen fully replaces the reaction system gas, reacting for 4-6 hours to obtain a modified product solution; S3: adding triethanolamine to the modified product solution, and cooling naturally, then adding acetone for cyclic washing 2-3 times, and drying to obtain; The mass ratio of styrene, glycidyl acrylate, butyl acrylate and N-hydroxymethyl acrylamide is (6-8): (1-2): (2-3): (30-35); The amount of triethanolamine added is 0.5-1wt% of the modified product solution; The initiator is azobisisobutyronitrile.

2. The high-strength slag-based cementitious material according to claim 1, characterized in that: The mass ratio of the blast furnace slag, silicate cement, fly ash and sodium bentonite is (55-65):(16-24):(7-10):(8-10).

3. The slag-based high-strength cementitious material according to claim 2, characterized in that: The mass ratio of the blast furnace slag, the filler and the resin material is (55-65): (15-20): (10-14).

4. The high-strength slag-based cementitious material according to claim 3, characterized in that: The blast furnace slag is steel plant blast furnace slag; the blast furnace slag contains, by mass percentage, 30-35% SiO2, 35-40% CaO, 10-15% Al2O3, 5-8% MgO, and the balance is supplemented by CaCO3.

5. The slag-based high-strength cementitious material according to claim 4, characterized in that: The silicate cement is Type I silicate cement.

6. The slag-based high-strength cementitious material according to claim 5, characterized in that: The fly ash is Class I fly ash or Class II fly ash.

7. The slag-based high-strength cementitious material according to claim 6, characterized in that: The enhancer is at least one of triethanolamine, ethylenediamine, isopropanol, aluminum sulfate and calcium chloride.

8. The slag-based high-strength cementitious material according to claim 7, characterized in that: The sodium bentonite is coarse-grained sodium bentonite; the average particle size of the coarse-grained sodium bentonite is 0.5 to 1.5 mm.

9. A method for preparing a high-strength cementitious material based on slag according to any one of claims 1 to 8, characterized in that: S1: Grind blast furnace slag in a ball mill until the particle size is ≤0.1mm, then mix the blast furnace slag with all other raw materials except water and add them to a mixer, stir at a speed of 60-80rpm for 15-20min to obtain a mixture; S2: Mix the mixture with water, stir at a speed of 50-60rpm for 15-25min until it becomes a uniform slurry, and obtain a mixed slurry; S3: Pour the mixed slurry into a pre-prepared mold, vibrate to compact it, remove bubbles, and cure it at a temperature of 18-24℃ and a relative humidity of 95-100% for 22-26h for initial curing. After demolding, continue to cure for 28 days, during which the temperature and humidity are kept constant, and the mixture is obtained after completion.

Citation Information

Patent Citations

  • Impermeable chloride- ion- erosion -resistant concrete and preparation method thereof

    CN110510943A

  • High-ductility cement-based composite material and preparation method thereof

    CN117209228A

Cited By

  • Method for processing goaf of mechanized mining working face of vertical groove coal

    CN122014341A